Comparative study of ultrasonic and maceration extraction in enhancing antioxidant and SPF properties of green coffee beans serum - Firdaus, Stradivary; Permadi, Adi; Sulistiawati, Endah (Institut Teknologi Bandung, 2025)
This study investigates the efficiency of maceration and ultrasonic extraction methods for obtaining antioxidants from Arabica, Robusta, and Liberica green coffee beans. Ultrasonic extraction demonstrated higher yields and enhanced antioxidant activity, with Liberica exhibiting the most potent radical scavenging potential (lowest IC50 values), followed by Robusta and Arabica in 45.3706 ppm, 46.6647 ppm, 49.4257 ppm. Formulated serums derived from these extracts were evaluated for compliance with SNI 16-4399-1996 standards. Both methods produced serums with acceptable texture, homogeneity, pH levels, and active ingredient retention. However, ultrasonic-derived serums displayed superior microbial safety profiles, with significantly lower total plate counts. Viscosity analysis revealed higher values for maceration-derived serums, while Sun Protection Factor (SPF) evaluation indicated that serum of Liberica extract provided the highest UV protection. These findings emphasize the potential of ultrasonic extraction and Liberica green coffee beans in developing high-value cosmetic and pharmaceutical products, paving the way for further research into optimized extraction techniques and broader applications.